Early postoperative outcomes for pancreaticoduodenectomy before and after implementation of enhanced recovery after surgery (ERAS) protocol - Ling Q.Y.; Ariffin A.C.; Azman A.; Zuhdi Z.; Othman H.; Jarmin R. (Surgical Society of Northern Greece, 2024)
Indexed by Scopus